Cortical Foxp2 Supports Behavioral Flexibility and Developmental Dopamine D1 Receptor Expression. (11th November 2019) - Co, Marissa; Hickey, Stephanie L; Kulkarni, Ashwinikumar; Harper, Matthew; Konopka, Genevieve
Abstract: Genetic studies have associated FOXP2 variation with speech and language disorders and other neurodevelopmental disorders (NDDs) involving pathology of the cortex. In this brain region, FoxP2 is expressed from development into adulthood, but little is known about its downstream molecular and behavioral functions. Here, we characterized cortex-specific Foxp2 conditional knockout mice and found a major deficit in reversal learning, a form of behavioral flexibility. In contrast, they showed normal activity levels, anxiety, and vocalizations, save for a slight decrease in neonatal call loudness. These behavioral phenotypes were accompanied by decreased cortical dopamine D1 receptor (D1R) expression at neonatal and adult stages, while general cortical development remained unaffected. Finally, using single-cell transcriptomics, we identified at least five excitatory and three inhibitory D1R-expressing cell types in neonatal frontal cortex, and we found changes in D1R cell type composition and gene expression upon cortical Foxp2 deletion. Strikingly, these alterations included non-cell-autonomous changes in upper layer neurons and interneurons. Together, these data support a role for Foxp2 in the development of dopamine-modulated cortical circuits and behaviors relevant to NDDs.